Research Trends on Islamic Education Learning Intensity and Students’ Religiosity : Implications of Democracy in Education - Naqiba, Muhammad Izzan; Taqiyyuddin, Yusuf Mukhtar (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze research trends and knowledge mapping on Islamic Education, Learning Intensity, and Students’ Religiosity during 2000–2025, with a particular emphasis on their implications for democracy in education. Using a bibliometric approach with data sourced from Scopus, 115 journal articles were analyzed through Biblioshiny for R to identify annual scientific production, leading authors, influential journals, collaboration networks, and thematic developments. The findings reveal a significant increase in publications after 2019, with dominant contributions from social sciences and humanities, and highlight interconnected themes such as religiosity, spirituality, ethics, and global issues like digital transformation and moral crises. The novelty of this study lies in integrating bibliometric mapping with democratic values in education, showing that Islamic education not only strengthens students’ religiosity but also promotes civic values such as tolerance, justice, and inclusivity. These insights provide both theoretical and practical contributions for policymakers, educators, and curriculum developers in shaping effective Islamic education that is relevant to global challenges and supportive of democratic principles in education